2010
DOI: 10.1084/jem.20092253
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota innate stimulation is a prerequisite for T cell spontaneous proliferation and induction of experimental colitis

Abstract: Little is known about how the microbiota regulates T cell proliferation and whether spontaneous T cell proliferation is involved in the pathogenesis of inflammatory bowel disease. In this study, we show that stimulation of innate pathways by microbiota-derived ligands and antigen-specific T cell stimulation are both required for intestinal inflammation. Microbiota-derived ligands promoted spontaneous T cell proliferation by activating dendritic cells (DCs) to produce IL-6 via Myd88, as shown by the spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
192
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 63 publications
10
192
0
1
Order By: Relevance
“…43 An elegant study by Feng et al demonstrated that microbiotaderived innate and TCR specific signals are both required for the induction of disease using a murine model of IBD. 77 Accordingly, it was shown that homeostatic proliferation of transferred T cells were only observed in SPF but not in GF Rag 2/2 mice, indicating that the presence of the gut microbiota is required for the T cell proliferation. This microbiota-mediated T cell proliferation requires a MyD88-dependant IL-6 induction in DCs.…”
Section: Gut Microbiota and Autoimmunitymentioning
confidence: 99%
“…43 An elegant study by Feng et al demonstrated that microbiotaderived innate and TCR specific signals are both required for the induction of disease using a murine model of IBD. 77 Accordingly, it was shown that homeostatic proliferation of transferred T cells were only observed in SPF but not in GF Rag 2/2 mice, indicating that the presence of the gut microbiota is required for the T cell proliferation. This microbiota-mediated T cell proliferation requires a MyD88-dependant IL-6 induction in DCs.…”
Section: Gut Microbiota and Autoimmunitymentioning
confidence: 99%
“…8B, are responsible for the induction of colitis when transferred in the absence of Treg cells. Antigenic peptides derived from the enteric bacteria and presented by MHCII molecules have been shown to be responsible for this TCR-driven fast proliferation whereas the slow proliferation is independent of MHCII molecules and IL-7-driven [26][27][28][29][30]. We took advantage of this model to determine whether upon transfer into Cd3e 5/ 5 x MHCII / mice, MLN-resident inflammatory M s isolated from MHCII-sufficient, colitic mice were capable of rescuing the fast proliferation of cotransferred CD4 + T cells and their differentiation into IFN-γ-producing effectors.…”
Section: Mln-resident M S From Colitic Mice Induce Ifn-γ-producing Efmentioning
confidence: 99%
“…The second type of LIP is thought to be more dependent on TCR-Ag-MHC interactions and leads to the rapid division of T cells and the upregulation of activation markers such as CD44. This fast proliferation is referred to as spontaneous proliferation and is similar to cognate Ag-induced proliferation (6), except that the peptide Ags involved in this signal are thought to be either self-or commensal-derived as the absence of the microbiota in germ-free mice virtually abolished the spontaneous proliferation of transgenic CD4 T cells (7). Additional evidence for the involvement of peptide-loaded MHC is that the complexity of the TCR repertoire influences the extent of proliferation, with only polyclonal T cells being able to inhibit the proliferation of T cells in lymphopenic hosts (8,9).…”
Section: T Cells Are Maintained By Survival Signals Such As Cytokinesmentioning
confidence: 99%
“…The two factors known to be involved in stimulating LIP are cytokines such as IL-7 and TCR-self-Ag MHC interactions (7,27). Whether costimulatory molecules play a role in promoting LIP is not clear because one group showed that CD4 T cell LIP is enhanced by CD28 signals (11), whereas another report showed that CD28, CD40, and 4-1BB signals are not required for LIP (10).…”
Section: Splenic Cd45 + Cd11c + Cells Partially Rescue Spontaneous T mentioning
confidence: 99%